2006
DOI: 10.1115/1.2739621
|View full text |Cite
|
Sign up to set email alerts
|

Forced Convection Heat Transfer and Hydraulic Losses in Graphitic Foam

Abstract: Experiments and computations are presented to quantify the convective heat transfer and the hydraulic loss that is obtained by forcing water through blocks of graphitic foam (GF) heated from one side. Experiments have been conducted in a small-scale water tunnel instrumented to measure the pressure drop and the temperature rise of water passing through the foam and the base temperature and heat flux into the foam block. The experimental data were then used to calibrate a thermal non-equilibrium finite-volume m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Such features will undoubtedly have an impact on the flow field, thereby influencing the observed permeability. This may serve to explain why the results for 88% reported by Straatman et al [26] are of the same magnitude as those predicted using the present model for 80%. Also included for comparison in Fig.…”
Section: Momentum Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Such features will undoubtedly have an impact on the flow field, thereby influencing the observed permeability. This may serve to explain why the results for 88% reported by Straatman et al [26] are of the same magnitude as those predicted using the present model for 80%. Also included for comparison in Fig.…”
Section: Momentum Resultssupporting
confidence: 79%
“…Klett et al [25] ran experiments on POCO™ foam of 75% porosity, while the experimental results shown from Straatman et al [26] correspond to a porosity of 88%. Though the results are in reasonable correspondence with the current predictions, physical SVP porous media is known to have non-spherical pores, jagged pore windows and blocked regions, all of which will disrupt the flow.…”
Section: Momentum Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The plots in The results show that, for an air velocity of 1 m/s, the thin layer of foam can increase the heat transfer by a factor of three even if the foam ligaments have a conductivity of only 10 W/mK. The reason is that the ligaments are working as highly efficient fins [26]. The heat transfer in the porous channel is enhanced by the higher velocity due to restrictions in flow area and the thermal conductivity of the foam ligaments; but in this case the primary cause for the enhancement is the extended surface area available for convection.…”
Section: Effect Of Foam Ligament Conductivitymentioning
confidence: 88%
“…At high velocities, the quadratic term in the Darcy-Forchheimer equation cannot be neglected and the flow regime is "non-Darcy". Equation (10) has been used to determine K and c f from experimental measurements of pressure drop and uniform filter velocity for a large variety of porous materials: aluminum, nickel and carbon foams [21], compressed aluminum foam [25] and carbon foam [26]. Experimental testing on aluminum foams showed that permeability of a porous material is a strong function of porosity and pore size and inertial coefficient is influenced by the solid phase shape and pore structure [23].…”
Section: Volume-averaged Fluid Flow Modelmentioning
confidence: 99%